Effect of xylitol varnishes on enamel remineralization of immature teeth: in vitro and in situ studies - Vanessa Lira SIQUEIRA; Gabriela Santos BARRETO; Emilly Bezerra Vieira SILVA; Talita Vieira da SILVA; Denis Gomes do NASCIMENTO; André VERONEZI; Marcela Charantola RODRIGUES; Marília Afonso Rabelo BUZALAF; Cristiane de Almeida Baldini CARDOSO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract We evaluated the efficacy of xylitol varnishes on the remineralization of newly erupted permanent and deciduous teeth in vitro and in situ. Human enamel specimens were randomly allocated to 8 groups (n = 15/group). Artificial caries lesions were produced and enamel alterations were quantified by surface/subsurface hardness and transverse microradiography. The blocks were then treated with the following varnishes: DuraphatTM; 20 wt% xylitol (146 μm) varnish; 20 wt% milled xylitol (80 μm) varnish, and placebo varnish, and removed after 6 h of immersion in artificial saliva. In vitro the blocks were subjected to pH-cycles for 8 days. In situ fifteen subjects wore palatal appliances containing four pre-demineralized and treated enamel specimens, for 5 days. Data were statistically analyzed by ANOVA/Tukey and Kruskal-Wallis/Tukey's test (p < 0.05). The %SHR in both studies was significantly increased by xylitol and Duraphat™ varnishes when compared to placebo. Considering subsurface remineralization, only the xylitol varnishes were able to significantly reduce the enamel lesion. Xylitol varnishes can be promising alternatives to promote enamel remineralization of newly erupted permanent and deciduous teeth.